Kepastian Hukum dalam Pengaturan Perkawinan Antaragama di Indonesia: Tantangan Pendaftaran Perkawinan Berdasarkan Hukum Nasional - Jamil, Jamil (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
Marriage constitutes a fundamental constitutional right and serves as an essential institution for protecting family life. However, the legal status of interfaith marriage remains one of the most contested issues in Indonesian family law due to the absence of explicit statutory regulation and inconsistent judicial and administrative practices. This study examines the legal certainty surrounding the implementation and registration of interfaith marriages under Indonesia's national legal framework. Employing normative legal research, the study analyzes constitutional provisions, statutory regulations, judicial decisions, and relevant legal doctrines using statutory and conceptual approaches. The findings reveal that the absence of comprehensive legislation has created legal uncertainty regarding the procedures, requirements, and authorities responsible for registering interfaith marriages. Consequently, many couples resort to overseas marriages, unregistered marriages, religious conversion solely for administrative purposes, or litigation to obtain legal recognition. The fragmented regulatory framework has also generated inconsistent interpretations among marriage registrars and courts, undermining the constitutional principles of legal certainty, equality before the law, and protection of citizens' civil rights. This study argues that harmonizing marriage legislation with constitutional guarantees is essential to establish a clear, uniform, and legally certain registration system for interfaith marriages while balancing religious values and constitutional rights within Indonesia's pluralistic legal order.